Juvenile Facility Staff Contestations of Change. (December 2018) - Cox, Alexandra
This article explores juvenile facility frontline staff members' contestations of change of custodial practices aimed at reducing restraints, introducing trauma-informed practices, and downsizing juvenile facilities. Drawing from qualitative research about frontline staff members in a US state undergoing reform, the article points to the ways that the reforms challenge staff members' investments in behavioral control practices as a vehicle for achieving order and control in their everyday lives as workers. It also points to shifts in the broader political economy on punishment at the local, facility level, and the subsequent impact on staff member perceptions of order, control and criminality.